Grazing starting time in Neonotonia wightii under irrigation conditions - Ruiz, Tom?s E.; Febles, Gustavo; Bernal, G. (Cuban Journal of Agricultural Science, 2014)
Four grazing starting times (6, 7 ?, 9 and 10 ? months after sowing in September) were evaluated in a pure Neonotonia wightii cv Tinaroo (glycine) grassland using a random block design with four replications, under irrigation conditions during the dry season. Instantaneous stocking rate of 38 LCU/ha/d with a rotation interval of 35 and 49 d was used for the rainy and dry seasons, respectively, with occupation times of two and three days per season. In the first rotation it was shown that the lowest grass height was shown by the most delayed grazing starting time (P < 0.001). However, the highest legume and total yield was attained at 6 and 10 ? months (P < 0.001). In the last rotation, the lowest grassland height, as well as total and glycine yield, was the starting time of nine months (P < 0.001). The highest values were attained with the treatment at 7 ? months. On concluding the first grazing year, the starting time at six months did not produce damages to the legume grassland, since there were no differences for weed yield and presented the highest values of glycine (P < 0.01). At the ending of the experiment, when all treatments had the same number of rotations, there was no effect of the studied grazing starting times regarding weed yield. For glycine, the lowest yield was for six months (P < 0.01). Concerning total yield, although the highest value (P < 0.01) was demonstrated for the 10 ? month treatment, this had greater incidence of weeds. It is concluded that under irrigation conditions, productive grasslands of glycine, stables in time, can be attained when grazing starts 7 ? months after sowing. Key words: Neonotonia wightii, establishment, grazing starting time, irrigation